2021
DOI: 10.4103/ijo.ijo_1204_21
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcome of full-thickness macular hole secondary to tractional retinal detachment in proliferative diabetic retinopathy

Abstract: Purpose: To evaluate the surgical outcome of full-thickness macular hole (FTMH) secondary to active fibrovascular proliferation (FVP) and tractional retinal detachment (TRD) in eyes with proliferative diabetic retinopathy (PDR), and factors influencing the outcome. Methods: This retrospective study included the patients who underwent vitrectomy for FTMH secondary to PDR TRD from 2016 to 2020. Anatomical and visual outcomes were analyzed after six months along with the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…There is ongoing debate in the literature on the role of ILM peeling, with Yeh et al 2 (n = 23 eyes) noting that PPV with concurrent ILM peeling did not affect the rate of successful hole closure, while Karimov et al 6 (n = 14 eyes) supported the value of standard ILM peeling for the restoration of macular anatomy and function. More recent literature from Babu et al 8 (n = 18 eyes) compared macula-off combined RD and macula-threatening RD and found that good anatomic and visual outcomes can be achieved after PPV with ILM peeling and SRF drainage in eyes with an MH associated with PDR and TRD. It is possible that different types of MHs in the setting of fibrovascular proliferation might benefit from ILM peeling, while in others it is not essential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is ongoing debate in the literature on the role of ILM peeling, with Yeh et al 2 (n = 23 eyes) noting that PPV with concurrent ILM peeling did not affect the rate of successful hole closure, while Karimov et al 6 (n = 14 eyes) supported the value of standard ILM peeling for the restoration of macular anatomy and function. More recent literature from Babu et al 8 (n = 18 eyes) compared macula-off combined RD and macula-threatening RD and found that good anatomic and visual outcomes can be achieved after PPV with ILM peeling and SRF drainage in eyes with an MH associated with PDR and TRD. It is possible that different types of MHs in the setting of fibrovascular proliferation might benefit from ILM peeling, while in others it is not essential.…”
Section: Discussionmentioning
confidence: 99%
“…Yeh et al 2 and Kurihara et al 3 reported that ILM peeling is not necessary for hole closure and resolution of persistent diabetic macular edema. In contrast, findings in studies by Karimov et al 6 and Babu et al 8 suggest that standard ILM peeling can help restore the anatomy and function of the macula by ensuring complete removal of the remnant vitreous sheet and tractional membranes and also helps provide relief from tangential traction. Mason et al 9 specifically looked at MHs in the setting of concurrent TRD and found that repair of TRDs related to MHs can be achieved via PPV, complete membranectomy, and intraocular gas placement.…”
Section: Introductionmentioning
confidence: 90%
“…Complete ERM removal without ILM peeling may be sufficient for eyes with moderate-to-high macular elevation [ 5 ]. The standard ILM peeling technique can successfully treat most cases and achieve better anatomical and visual outcomes [ 3 , 8 ]. Traction release by the surgery and the pre-proliferative environment could help promote MH closure [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pars plana vitrectomy (PPV) and internal limiting membrane peeling (ILMP) and gas tamponade remains the treatment basis for both Idiopathic and secondary macular hole (MH) though Gass' hypothesized that tangential vitreomacular traction was the key factor in the pathogenesis of Idiopathic MH (Gass, 1988). Good visual outcome with 88% of type 1 closure of MH has been noted after surgical intervention in MH secondary to tractional retinal detachment (Babu et al, 2021). There are various techniques described in literature including major surgical interventions (Reid et al, 2020) and minor procedures like gas tamponade injections for treatment of persistent MH (Iwase and 2007) (Kannan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%